Drug delivery for age-related bone diseases: From therapeutic targets to common and emerging therapeutic strategies - Jiaming Bi; Jiawei Zeng; Xiaohao Liu; Chuzi Mo; Mingyan Yao; Jing Zhang; Peiyan Yuan; Bo Jia; Shuaimei Xu (Elsevier, 2024)
With the accumulation of knowledge on aging, people have gradually realized that among the many factors that cause individual aging, the accumulation of aging cells is an essential cause of organ degeneration and, ultimately, age-related diseases. Most cells present in the bone microenvironment gradually age over time, leading to an imbalance of osteogenesis, osteoclastogenesis, adipogenesis, and chondrogenesis. This imbalance contributes to age-related bone loss and the development of age-related bone diseases, such as osteoporosis. Bone aging can prolong the lifespan and delay the development of age-related diseases. Nanoparticles have controllable and stable physical and chemical properties and can precisely target different tissues and organs. By preparing multiple easily modified and biocompatible nanoparticles as different drug delivery carriers, specifically targeting various diseased tissues for controlled-release and sustained-release administration, the delivery efficiency of drugs can be significantly improved, and the toxicity and side effects of drugs can be substantially reduced, thereby improving the therapeutic effect of age-related bone diseases. In addition, other novel anti-aging strategies (such as stem cell exosomes) also have significant scientific and practical significance in anti-aging research on age-related bone diseases. This article reviews the research progress of various nano-drug-loaded particles and emerging anti-aging methods for treating age-related bone diseases, offering new insights and directions for precise targeted clinical therapies.